UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS X TEKNIK KOMPUTER JARINGAN (TKJ) SMK NEGERI 3 YOGYAKARTA DENGAN MODEL PEMBELAJARAN PROBLEM POSING SECARA BERKELOMPOK - Anton Purnomo; AA Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2014)
The purpose of this research is to improve the ability to think creatively and mathematics achievement of tenth grade students of Engineering Computer Networking SMK Negeri 3 Yogyakarta with models of learning in group problem posing. This research is a classroom action research (CAR) conducted in two cycles. The subjects were students of tenth grade Engineering Computer Networking, amounting to 36 students. Data collection techniques in this study using observation, testing, interviews and documentation. Results of this study after using problem posing learning model showed an increase in the ability to think creatively and math achievement of students. (1) The mean score of students' creative thinking abilities increase of 61.46% on the pretest to 80.55% in the first cycle test and increased again to 87.5% in the second cycle. Criteria for each aspect of the ability to think creatively in the second cycle varies. Aspects smooth on very high criteria. Aspects of high flexibility in the criteria. Aspects of the criteria are originality. Aspects of detail on very high criteria. (2) There is an increase in the percentage of student mastery of 75% of all students achieving â‰¥ 75 KKM. It is evident from the increase in 44.44% (16 students completed) on the pretest increased to 58.33% (21 students completed) in the first cycle test and increased to 77.78% (28 students completed) I. Model of learning in group problem posing able to be an alternative learning models improve the ability to think creatively and mathematics achievement.